African traders and economic development in Ghana - Garlick, Peter C. (Oxford : Clarendon Press, 1971)
This is a study of traders in Ghana with data collected in 1957-62 based on interview of 450 major traders in Ghana. The main topics covered are the traders' backgrounds (tribe, education, training, and experience), types of business, credit, suppliers, customer$1 (Bs competition, social status, and motivation.s
Includes index.
Includes bibliographical references: p. 157-165.
lje 28/09/2018
Loans
Keywords: Economic development; Ghana